On the twin deficits hypothesis: is Malaysia different? - Lau, Evan; Baharumshah, Ahmad Zubaidi (Universiti Putra Malaysia Press, 2004)
This paper discusses the on-going debates surrounding the issue of twin deficits in Malaysia. The statistical technique advocated by Toda and Yamamoto (1995) for handling economic variables that might spuriously move together is utilized to examine the long run causal relationships between budget and current account deficits. We examine more than the three decades of time series data to answer the question of whether the budget deficit had led to current account deficit. The empirical result reveals the presence of bi-directional causality between the two deficits in Malaysia. It is this finding that makes Malaysia different from the major industrialized countries. On the one hand, we find that the causal relationship is from budget to current account deficits providing evidence of twin deficits phenomena. On the other hand, the reverse causation as detected in this study tends to suggest some evidence of current account targeting. Therefore, policy to curb 'chronic' current account deficit cannot be achieved if the policy markers simply rely on curtailing budget deficit.